Enhancing students' mathematical problem-solving skills through the teams games tournament model with domino card media - Mardiyati, Dikalila Putri; Nugraheni, Nursiwi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Students’ weakness in understanding and applying mathematical concepts is a problem that is often encountered. Therefore, students need to develop essential skills such as problem-solving. Other reasons are also caused by the conventional learning system that is still applied today. This study was conducted to develop domino card media with the Teams Games Tournament (TGT) model to enhance the mathematical problem-solving skills of 5th-grade students, especially in greatest common divisor (GCD) and least common multiple (LCM) learning. This development research adopts the Borg and Gall model. The media obtained a score of 93.3% from material experts, 96.6% from language experts, and 92.2% from media experts. Based on the t-test results, this media was proven to affect a Sig score. (2-tailed) .000 < 0.05. Proving that H0 is rejected and H1 is accepted. This media has also proven effective through the n-gain test, with a score of 0.78 for small-scale and 0.82 for large-scale trials. This score is in the high category because g > 0.70. Thus, this domino card media is appropriate for improving students’ mathematical problem-solving skills. This research offers a fun learning solution, encourages active participation, and helps students understand mathematical concepts more meaningfully.